Topeng Sidakarya Dance; A Man who made it a success - Rizky Januar (Bali Tourism Board, 2020)
Topeng Sidakarya dance is a masked wali dance originated from the 16th century. A typical old art performance that utilises a mask to express the figure's character. It is believed the art was choreographed after a brief visit of Brahmana Keling, a sage from eastern Java to Bali at the time King Dalem Waturenggong was reigning Gelgel Kingdom. The tour of Brahmana keling to the grand ritual held in the 16th century by king Dalem Waturenggong gave birth to Topeng Sidakarya dance; An art to dedicate Brahmana Keling’s service for Gelgel kingdom. His service had led Bali to reach its prosperous time for an extended period. The dance is recognised by its unique mask characteristics: a white-based colour mask, squinting eyes, black or white moustache, smiling expression and exaggerated overbite teeth. Topeng Sidakarya dance served as a complement of religious rituals based on king Dalem Waturenggong’s decree for the future generation. It is compulsory to perform the sacred art as it carries a symbol that the ceremony has been well-acted, and the organiser would meet their expectation for the ritual.